RESEARCHING OF HORMONE PARAMETERS OF FOOTBALL PLAYERS (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to examine the hormonal changes of players competing in different leagues. A total of 21 soccer players (play 20 matches) who play in professional leagues train 4.88±1.32 days a week, and 36 soccer players (play 20 matches) who play in amateur leagues train 2.45±1.12 days a week participated in the study. The study was carried out at the end of the 2020-2021 soccer season. The data were analyzed using the SPSS 22 package program. The independent t-test was used to compare the hormonal parameters. A significant difference was found in the height of the football players participating in the study (p<0.05). No significant difference was found in age, athlete's age, body weight, BMI and other hormonal parameters (p>0.05). The main finding of the study is that there is no difference in endocrine markers between professional and semi-professional football players, despite the number of days they train. The reason why there is no difference may be due to the fact that semi-professional footballers play in a lower league and the number of matches is equal, even if the training times are different. To mention the importance of the study, it is to constantly monitor the endocrine parameters of the football players, to determine the training loads of the football players according to the league and level, to prevent injuries, to follow the performance and to ensure that there is no overtraining.